The Role of Software in the Field of Art and Culture (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Information and communication technologies have become an integral part of our lives. They have changed our social habits and changed our perception of ourselves and the world around us - affecting human behavior. Art works the same, even more, because it can provide unexpected performances of the world and thus provoke new insights. By utilizing new media resources, students can expand their creativity through digitally simulated information. Flexibility of digital data is what makes new media of vital importance for the teaching of fine arts. By using automated media tools and graphic software, students can quickly see the results of their ideas. By applying ICT, the amount of work in creating visual information is minimized, so students will have more time for creativity, collaboration, research and assessment.